SYNTAX STRUCTURE IN MANDUROS' UTTERANCE AS BASIC WRITING SKILL - Diana Mayasari; Nanda Rizki Ardhana (Universitas Negeri Surabaya, 2022)
Writing skills are important skills in the world of education. Linguistics is an inseparable part of these skills. The syntax is a language that studies syntactic functions, roles and categories as a basis for writing skills. This study aimed to describe the function, role, and syntactic categories of the Manduro community. The research method used is descriptive. Data collection techniques used are interviews and documentation. The analysis technique uses inductive techniques by checking the validity of the data using triangulation techniques. The results of the study found that syntactic functions consist of subject, predicate, object, description, and complement. The word category consists of nouns and noun phrases, verbs, adjectives and adverbial verbs and phrases, while roles have the role of doers and responders for the subject, actions for predicates, goals and results for objects. The study results are expected to be useful for developing syntactic courses, especially for students in Indonesia.